Electrochemical Degradation Study of 4‐Chlorophenol Using Magnesium Ferrite Catalysts Prepared by Solution Combustion - Aromal Ashok (21633119) (2025)
Electrochemical degradation of 4‐chlorophenol (4‐CP) was investigated using a rotating disk electrode (RDE) over magnesium ferrite (MgFe2O4), iron‐oxide and magnesium‐oxide in presence of 4‐CP in varying concentrations of 25, 50, and 75 mg/L. The objective of this study is to evaluate the effectiveness of these catalysts in achieving high current densities during the degradation process, and to understand their relation with the structural properties of the catalysts obtained from standard characterization techniques. Our results indicate that the MgO catalyst shows a poor current density for electrocatalytic degradation of 4‐CP. However, when MgO is used in presence of iron oxide, as in MgFe2O4, a high current density for 4‐CP degradation is observed, indicating the synergistic role of Mg-Fe system in improving catalytic activity. On the other hand, iron oxide alone showed the highest current density, however, most of which is expected to be associated with water splitting as opposed to 4‐CP degradation. Our findings highlight the potential of magnesium ferrite based mixed oxide catalysts in environmental applications, and also provide insights into the role of Mg in modulating catalytic performance. Additionally, this work also emphasizes the role of implementing RDE technique in identifying suitable catalysts for studying 4‐CP degradation in wastewater. Other Information Published in: Energy Storage License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/est2.70129